Study of knowledge attitude practices and utilisation of existing health services by families with regard to newborn health at block level in rural India: a community based, cross sectional, observational study - Choudhary, Monica; Verma, Rahul; Jain, Shikhar (International Journal of Contemporary Pediatrics, 2019)
Background: The present study was undertaken to identify KAP gaps and the objective of the study were to assessment of utilization of existing health service infrastructure at grass route level in rural community with regard to mother and neonatal care. Methods: A community based cross-sectional observational study. About 50 mother neonate pair residing in villages under study belonging to Dewas district, Madhya Pradesh. Results: Age old customs and practices of large family (80%), adolescent marriages (30%), high fertility (50%), poor housing and sanitation (48% or more) are still widely prevalent in rural India. Positive impact of NRHM with launch of JSSY and NSSK was seen in utilization of ANC services among beneficiaries with 100% ANC registrations, 98% institutional deliveries and 100% deliveries conducted by trained health professionals, prompt referral to SNCU. Birth weight was not known in 36% neonates and 18% had not received BCG vaccination. 22% were low birth weight and 22% neonate’s required SNCU care. Government emergency transport facility in form of ambulance was either absent (36%) or not utilized (26%) by majority. Conclusions: Lacunae were seen to be persisting regarding awareness and utilisation of few components of maternal and neonatal health care especially in government sector in spite of launch of third phase of NRHM. This was evidenced by, lack of awareness of Obstetric USG facility at civil hospital, non-utilisation of ambulance service for transport, not knowing neonates birth weight and no neonatal follow up care and failure to vaccinate the neonate even till 3rd or 4th week of life.